Alzheimer's disease - Germany - Hausner, Lucrezia; Frölich, Lutz (European geriatric medicine, 2010)
To illustrate the up-to-date pattern of patient management and adherence to common clinical guidelines in daily practice in Germany, a standardised example of an outpatient with reasonable suspicion to dementia was evaluated according to personal experience and published evidence from original studies and national guidelines regarding standard diagnostic procedures, the role and diagnostic steps of the family physician (FP), the access to a specialists treatment, perceptions on dementia in the lay public, drug treatment habits and the role of Alzheimer's associations. In Germany, FPs are generally the first to be approached in the case of emerging cognitive deficits. Their standard diagnostic procedures usually comprise a physical examination including a short psychiatric and neurological examination, blood laboratory tests and the assessment of history from relatives or caregivers. The specialists in private practice in the field of neuropsychiatry evaluate a demented subject in more detail after referral from FPs. Diagnostic evaluation frequently includes tests and rating scales, and also neuroimging of the brain by CT or MRI. Acetylcholinesterase inhibitors (AChE-I) and memantine, several nootropics and Ginkgo biloba are readily available and are all reimbursed by health insurances, if used according to their indication. Due to an increasing awareness of dementia within the lay public, Alzheimer's associations are active in Germany on a national and a regional level. In Germany, dementia is increasingly accepted as a medical condition among FPs and the lay public. Despite this increasing awareness, diagnostic and therapeutic practice is frequently not following current evidence-based guidelines and general management patterns of dementia should be more consistent and comprehensive.